Optimalisasi Deteksi Dini Hipertensi dan Penyakit Metabolik melalui Pemeriksaan Kesehatan Gratis dan Penyuluhan Kesehatan - Nurhardianti, Nurhardianti; Sapriana, Sapriana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2025)
Hypertension and metabolic diseases such as diabetes, high cholesterol, and uric acid are common health issues in society. These conditions often present no symptoms in their early stages, making early detection a crucial step in preventing more severe complications. This community service activity aimed to raise awareness of the importance of early detection of hypertension and metabolic diseases through educational outreach and free health check-ups. The methods included educational counseling and health screenings, such as blood pressure, blood glucose, cholesterol, uric acid, body weight, and body mass index measurements. The results indicated high community enthusiasm for participating in health check-ups and receiving health education. Most participants benefited directly by gaining an understanding of their health conditions and the recommended follow-up actions. This activity successfully increased community awareness of the importance of early detection and prevention of non-communicable diseases.